Eﬀect of the real multilateral exchange rate on exports and imports of Peru in the period 1991 - 2019 - Pozo Castillo, Wendy (2020)
This research paper seeks to determine the eﬀect of the real multilateral exchange rate on Peru's Exports and Imports in the period 1991 - 2019. The data used to perform the corresponding analysis are real monthly under the Unit Root Test (Dickey Fuller) and Johansen Cointegration Test in order to identify the existence of cointegration between the variables. The results indicate that the eﬀect of the real multilateral exchange rate on exports was 1.00 and show a negative eﬀect compared to imports that was -1.11. Finally, among the mechanisms that can be suggested is maintaining stable macroeconomic policies and seeking to diversify Peru's foreign trade with other countries to increase exports of national goods.